Quality Evaluation of Mechanically Washed and Polished Turmeric Rhizomes - Arora, M; Seghal, V K; Sharma, S R (Journal of Agricultural Engineering, 2007)
The quality of turmeric powder depends upon the initial quality of rhizomes and the practices adopted in various post harvest operations. Washing and polishing are two primary processes for quality enhancement. Turmeric rhizomes were mechanically washed in a rotary machine at varied speed and time and evaluated for microbiological washing efficiency and bruising. For optimized parameters such as 2.2 min washing time at 47.2 rpm rotational speed of the machine, the microbiological efficiency was 87.2% with negligible bruising. At optimum polishing (78%) performance parameters of 40 rpm rotational speed for 20 min, the color improved from dark yellowish brown to desirable olive yellow color (2.5 YR 6/6, Munsell color chart rating), with increase in the surface smoothness (Coefficient of external friction on G.I sheet reduced from 0.487 to 0.436), and also resulted in improvement in the microbiological quality. Mechanical polishing reduced the surface microflora by half. The total fungi reduced from 7050 to 3220 cfu/g, bacterial count decreased from 1500 to 770 cfu/g and coli-forms reduced from 200 to 110 cfu/g, thus enhancing the final quality of turmeric rhizomes.